2016
DOI: 10.1364/oe.24.007670
|View full text |Cite
|
Sign up to set email alerts
|

Hollow core anti-resonant fiber with split cladding

Abstract: An improved design for hollow core anti-resonant fibers (HAFs) is presented. A split cladding structure is introduced to reduce the fabrication distortion within design tolerance. We use numerical simulations to compare the Kagome fibers (KFs) and the proposed split cladding fibers (SCFs) over two normalized transmission bands. It reveals that SCFs are able to maintain the desired round shape of silica cladding walls, hence improving the confinement loss (CL) compared to the KF and is comparable to that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Contrarily to HC-PBGs, surface modes can easily be suppressed in HC-AR fibers [32] and, thus, SSL can be reduced by one order of magnitude [6,29]. In order to control the modal content and attenuation, several types of HC-AR fibers have been proposed, investigated, and fabricated, including HC-AR fibers with circular anti-resonant tubes [4,10,[38][39][40][41], "ice-cream cone" shape anti-resonant tubes [41,42], elliptical anti-resonant tubes [43], nested anti-resonant tubes [5,6,11], as well as cladding tubes with even more complex shapes [44]. Recently, Debord et al [38] demonstrated a single ring HC-AR fiber with 8 non-touching circular tubes with a propagation loss of 7.7 dB/km at 750 nm and a bend loss of 0.03 dB/turn at a bend radius of 15 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily to HC-PBGs, surface modes can easily be suppressed in HC-AR fibers [32] and, thus, SSL can be reduced by one order of magnitude [6,29]. In order to control the modal content and attenuation, several types of HC-AR fibers have been proposed, investigated, and fabricated, including HC-AR fibers with circular anti-resonant tubes [4,10,[38][39][40][41], "ice-cream cone" shape anti-resonant tubes [41,42], elliptical anti-resonant tubes [43], nested anti-resonant tubes [5,6,11], as well as cladding tubes with even more complex shapes [44]. Recently, Debord et al [38] demonstrated a single ring HC-AR fiber with 8 non-touching circular tubes with a propagation loss of 7.7 dB/km at 750 nm and a bend loss of 0.03 dB/turn at a bend radius of 15 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The simplified structure features a negative core curvature, a non-touching core boundary and one tube cladding layer 16, 19, 22, 23 , thus often being named as Tube Lattice Fiber (TLF) 2426 . The negative curvature is found to enhance the coupling inhibition between the core and cladding modes 2729 while the non-touching core boundary helps to reduce a loss caused by the Fano-resonance 21, 30 . Moreover, the simple one ring cladding is proven sufficient to offer efficient light guidance 18, 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The other type of HC-PCF is the so-called Hollow-Core Anti-Resonant Fibers (HC-ARFs), the guiding property relies of which on the combination of anti-resonance and inhibited coupling to low density of states cladding modes [7,8]. The HC-ARF has received ever-increasing interest thanks to its multiple broad transmission bands [7,9], simple and flexible cladding structures [10][11][12][13] and relatively low transmission loss [8,[14][15][16]. The HC-ARFs show promising prospects in applications such as delivering light with a wide spectral range from ultra violet to mid-infrared [17,18], an optofluidic system [19,20] and light gas interaction [21].…”
Section: Introductionmentioning
confidence: 99%